2022
DOI: 10.1039/d2ra03703c
|View full text |Cite
|
Sign up to set email alerts
|

In silicoinvestigation of the role of vitamins in cancer therapy through inhibition of MCM7 oncoprotein

Abstract: An in silico drug repurposing strategy combining docking and molecular dynamics simulation identifies the anticancer potential of vitamins targeting the MCM7 protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Thus, quercetin can act as a better inhibitor for the MMP‐9 receptor. [ 54 ] Protein–ligand interactions between the ligands and the MMP‐9 receptor were analyzed using BIOVIA DSV, [ 55 ] as depicted in Figure and the binding affinity of the selected drug and Quercetin with the MMP‐9 receptor are tabulated in Table 1 along with their structures. Through the in silico studies, we have observed that quercetin may act as a better MMP‐9 inhibitor as it shows a good binding affinity of 8.8 kcal mol −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, quercetin can act as a better inhibitor for the MMP‐9 receptor. [ 54 ] Protein–ligand interactions between the ligands and the MMP‐9 receptor were analyzed using BIOVIA DSV, [ 55 ] as depicted in Figure and the binding affinity of the selected drug and Quercetin with the MMP‐9 receptor are tabulated in Table 1 along with their structures. Through the in silico studies, we have observed that quercetin may act as a better MMP‐9 inhibitor as it shows a good binding affinity of 8.8 kcal mol −1 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 72 ] Before the docking, the structure of the predicted receptor underwent pre‐processing using AutoDock MGL Tools 1.5.6. [ 55 ] This pre‐processing included the removal of water molecules and the addition of polar hydrogen groups to the receptor's structure. Subsequently, the ligands were docked to the receptor, and the docking simulations were carried out using the Lamarckian Genetic Algorithm (LGA) in AutoDock Vina v1.2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ModRefiner, a high resolution protein structure refinement server was used for the refinement of best modeled protein [12] . The best refined model was selected on the basis of the more 90 % of residues fall in the most favored region of Ramachandran plot by using ProCheck [13] . For identification of highly conserved, exposed, and functional residues ConSurf server was used [14] , [15] .…”
Section: Methodsmentioning
confidence: 99%